Quality of life as a predictor of postoperative outcome following revascularization of peripheral arterial disease - Ghosh, Shantonu Kumar; Majumder, Alpana (International Surgery Journal, 2017)
Background: Peripheral arterial disease (PAD) is associated with a significant morbidity and mortality. In addition to physical factors, patient’s quality of life (QOL) i.e. individual’s physical health, psychological state, level of independence, social relationships, and their relationship to salient features of their environment also influence on post-operative outcome and there by long term survival after surgery. Health related quality of life (HRQOL) is the extent to which one’s usual or expected physical, emotional and social well-being are affected by a medical condition or its treatment. The purpose of this study was to compere the health-related quality of life before and after revascularization following PAD and to identify the relationship with post-operative outcome following revascularization. Methods: Cases were divided into two groups according to presence and absence of ulceration in foot. Those patients having claudication with ulceration were enrolled in group A and those having claudication without ulceration were enrolled in group B. Data were collected from both groups preoperatively and during follow up at 1 month and 3 months by interviewing the patient according to SF-36. Results: Two groups with preoperative poorer HRQOL (n=25) or optimum HRQOL (n=25) were compared. Postoperative outcome was found poor in Group A compered to Group B. In both groups, there was little improvement in quality of life after 1 month of surgery. In Group A QOL improved a little between 1 to 3 months postoperatively. But in Group B, there was significant improvement of postoperative QOL between 1 and 3 months. Overall, Group A patients had preoperative symptoms more prominent and their postoperative outcome was also poor. Conclusions: Those patients who had preoperative optimum quality of life had better postoperative outcome. From this study it can be concluded that quality of life can be used as a predictor of postoperative outcome in peripheral arterial disease patients.